Cutaneous adverse events associated with the efficacy and benefit of immune checkpoint inhibitors: a systematic review and meta-analysis - Zhang, Li; Gao, Yunge (Frontiers in Oncology, 2025)
ObjectiveCutaneous immune-related adverse events (cirAEs) are associated with improved survival in tumor patients undergoing immune checkpoint inhibitors (ICIs) therapy, while inconsistent evidence has been reported across tumor subtypes. This study aimed to evaluate the association of cirAEs and their subtypes with cancer prognosis.DesignSystematic review and meta-analysis.MethodsFour databases including Cochrane Library, Embase, PubMed and Web of Science were searched for original publications from inception to April 30, 2024. A meta-analysis was carried out for overall survival (OS) and progression-free survival (PFS) of patients, and pooled hazard ratios (HRs) with 95% confidential intervals (CIs) were calculated. Subgroup analyses involving cirAEs subtype, cancer type, ICIs type, geographic region of patients, and study quality were performed.ResultsForty-five studies comprising a total of 26817 patients with ICIs treatment were included in the study. The occurrence of cirAEs was associated with prolonged OS (HR, 0.54 [95%CI, 0.46-0.63]; P < 0.001) and PFS (HR, 0.51 [95%CI, 0.43-0.60]; P < 0.001). Favorable survival was observed in patients with vitiligo, with the most pronounced OS (HR, 0.23 [95%CI, 0.18-0.33]; P < 0.001) and PFS (HR, 0.28 [95%CI, 0.21-0.38]; P < 0.001). Similarly, the prolonged OS (HR, 0.69 [95%CI, 0.64-0.74]; P < 0.001) and PFS (HR, 0.69 [95%CI, 0.58-0.82]; P < 0.001) in patients with rash. Significant benefit in OS were also observed in drug hypersensitivity or eruption, eczematous, lichenoid or lichen planus-like lesion, pruritus and psoriasis, but not in bullous pemphigoid, maculopapular and mucositis. Favorable survival was observed in patients with RCC, NSCLC and MM, with the most pronounced OS (HR, 0.22 [95%CI, 0.08-0.59]; P = 0.002) and PFS (HR, 0.22 [95%CI, 0.11-0.43]; P < 0.001) for RCC patients; and only OS benefit in HNSCC (HR, 0.64 [95%CI, 0.42-0.99]; P = 0.04). Subgroup analyses involving geographic region and study quality showed consistent results with the overall estimate confirming robustness.ConclusionsThe occurrence of cirAEs, especially in vitiligo and rash, predicted a significant survival benefits among tumor patients receiving ICIs therapy, especially in MM, RCC and NSCLC.